Optimalisasi dan pengembangan mesin penggembur tanah inovatif untuk meningkatkan produktivitas lahan kering - Ahmad Nurul Muttaqin; Uswatul Hasanah Mihdar; Rusdi Nur (Jurnal Teknik Mesin Indonesia, 2023)
The creation of a soil-loosening device that works well on dry terrain is the goal of this study. With this equipment, perhaps, human labor in construction and agriculture will be reduced and productivity will rise. In the machine assembly process, virtual assembly is carried out using Autodesk Fusion 360 software prior to the actual assembly phase. During assembly, the mounting frame for the combustion engine is joined to the main frame. Furthermore, sprockets are mounted on the two axles and wheels, and belt tensioners are added. This machine's blade is used to swiftly loosen the dirt. An area of thirty square meters was tested by machines on dry land, and each test took an average of 229.3 seconds to complete. The machine's time efficiency is greater than that of the earlier variants. In addition, factors including longevity, running costs, simplicity of maintenance, and environmental effect need to be carefully considered in this study. This development tool has a great deal of potential to improve the efficiency and productivity of the dry land soil loosening process. The research findings are expected to contribute to technological advancements in Indonesia's building and agriculture sectors.